2017
DOI: 10.1038/s41598-017-10766-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Evolution of Carbonaceous Aerosols during Dispersal of East Asian Haze

Abstract: Wintertime East Asia is plagued by severe haze episodes, characterized by large contributions of carbonaceous aerosols. However, the sources and atmospheric transformations of these major components are poorly constrained, hindering development of efficient mitigation strategies and detailed modelling of effects. Here we present dual carbon isotope (δ13C and Δ14C) signatures for black carbon (BC), organic carbon (OC) and water-soluble organic carbon (WSOC) aerosols collected in urban (Beijing and BC for Shangh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 60 publications
7
33
0
Order By: Relevance
“…Previous studies reported that for urban environments in China, the daily average PM 2.5 (particulate matter with aerodynamic diameter ≤ 2.5 μm) levels for January both of 2013 and 2014 were observed to be 10 times higher than the recommended daily maximum level (25 μg/m 3 ) of the World Health Organization (e.g., Andersson et al, ; Fang et al, ; Sheehan et al, ; World Health Organization ). The daily values during haze days are also much higher than China's new Ambient Air Quality Standards for daily PM 2.5 (35 and 75 μg m −3 for Category I and II zones, respectively; Chinese Ministry of Environmental Protection, ).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies reported that for urban environments in China, the daily average PM 2.5 (particulate matter with aerodynamic diameter ≤ 2.5 μm) levels for January both of 2013 and 2014 were observed to be 10 times higher than the recommended daily maximum level (25 μg/m 3 ) of the World Health Organization (e.g., Andersson et al, ; Fang et al, ; Sheehan et al, ; World Health Organization ). The daily values during haze days are also much higher than China's new Ambient Air Quality Standards for daily PM 2.5 (35 and 75 μg m −3 for Category I and II zones, respectively; Chinese Ministry of Environmental Protection, ).…”
Section: Introductionmentioning
confidence: 95%
“…High BC emissions in China is a contributing factor to the very high concentrations of aerosols during severe haze events (e.g., Ding et al, ; Fang et al, ; Qin & Xie, ). However, bottom‐up technology‐based emission inventories (EIs) are acknowledged to carry an uncertainty by factors of 2–4 for BC, with the uncertainty stemming largely from variations in BC emission factors (EF, mass of BC emitted per mass fuel consumed, or product produced) but also from uncertainties in activity estimates (e.g., energy consumption data; e.g., Bond et al, ; Lu et al, ; Wang et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiocarbon ( 14 C, half-life = 5,730 years) is a state-of-the-art tracer that can directly and clearly separate OC and EC into fossil (e.g., coal and petroleum) and nonfossil (e.g., BB and biogenic emissions) sources based on the fact that the fraction of modern carbon (f m ) is very close to 1 in nonfossil materials while the f m value in fossil fuels is 0 (Szidat, 2009). There is a growing number of 14 C-based studies in China Chen et al, 2013;W. Fang et al, 2017;Huang et al, 2014;J.…”
Section: Introductionmentioning
confidence: 99%